Strengthening Land Allocation Policies for Empowering Local Farmers in Palm Oil Plantations - Izmi Waldani; Fauzul Amri; Mhd Halkis; Hengki Andora; Kurnia Warman (Lex Publica, 2024)
This study investigates the implementation of the obligation to allocate 20% of plantation land to farmers from a jurisdictional perspective by using a case study of PT. Wanasari Nusantara in Kuantan Singingi Regency, Riau Province. The obligation, stipulated under the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 26 of 2007, aims to empower local communities and foster regional economic development. Employing an empirical legal research methodology, this study analyzes legal frameworks and qualitative data gathered through stakeholder interviews. The findings indicate that the company has not fully complied with its obligations, largely due to inadequate oversight and a lack of transparency in the management and expansion of Land Use Rights (Hak Guna Usaha or HGU). From the perspective of spatial planning law, land allocation policies are vital to ensure equitable access to land resources. However, these policies require stronger regulatory frameworks and enforcement mechanisms to achieve their objectives. The study concludes by recommending a comprehensive revision of supervision mechanisms and an enhanced governmental role to ensure effective implementation of land allocation policies. This approach is essential for achieving distributive justice and promoting sustainable social and economic development.